2019
DOI: 10.1016/j.critrevonc.2019.07.013
|View full text |Cite
|
Sign up to set email alerts
|

How do skeletal morbidity rate and special toxicities affect 12-week versus 4-week schedule zoledronic acid efficacy? A systematic review and a meta-analysis of randomized trials

Abstract: How do skeletal morbidity rate and special toxicities affect 12-week versus 4-week schedule zoledronic acid efficacy? A systematic review and a metaanalysis of randomized trials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…However, the optimal dosing intervals remain unclear. A randomized controlled trial (RCT) that compared 12-weekly zoledronic acid administration with 4-weekly zoledronic acid administration reported no signi cant difference in the incidence of SREs and a higher incidence of adverse events with 4-weekly zoledronic acid administration [23]. In breast cancer, zoledronic acid is administered every 12 weeks [24], but no speci c dosing interval is speci ed for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal dosing intervals remain unclear. A randomized controlled trial (RCT) that compared 12-weekly zoledronic acid administration with 4-weekly zoledronic acid administration reported no signi cant difference in the incidence of SREs and a higher incidence of adverse events with 4-weekly zoledronic acid administration [23]. In breast cancer, zoledronic acid is administered every 12 weeks [24], but no speci c dosing interval is speci ed for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, different results emerged from the ERA-223 [41] and the EORTC 1333/PEACE [42] phase III studies. In these trials, the new radiopharmaceutical's role has been debunked; in fact, to limit the risk of pathological fractures, radium-223 should not be administered together with classical BTAs and abiraterone plus prednisone or enzalutamide [42,43].…”
Section: Bone Targeting Agents In Hormone Sensitive and Castration Re...mentioning
confidence: 99%
“…According to the latest guidelines on skeletal metastases management, ZA should be administered endovenously at the dose of 4 mg every 4 weeks even if 12-weekly schedule does not seem to be inferior to standard administration in terms of reducing the risk of skeletal events [43][44][45]. On the other hand, denosumab should be given subcutaneously every 28 days at the dose of 120 mg. As for ZA, the 12-weekly schedule is an alternative treatment strategy [45].…”
Section: Bone Targeting Agents In Hormone Sensitive and Castration Re...mentioning
confidence: 99%
“…In general clinical practice, high-dose BPs are intravenously administered every 4 weeks after the start of administration; however, recently published studies showed non-inferiority of 12-week versus 4-week schedules of BP administration 22 . The administration interval 23 and the need for switching BPs 24 are still controversial.…”
Section: Scientific Reportsmentioning
confidence: 99%